Two Perspectives, One History: Western Colonialism in Indonesian and Malaysian History Textbooks - Wildan Insan Fauzi; Agus Mulyana; Wawan Darmawan; Dadan Wildan; Hany Nurpratiwi (Paramita: Historical Studies Journal, 2026)
Abstract: This study examines how Western colonialism is narrated in Indonesian and Malaysian history textbooks and compares the perspectives embedded in both national textbook traditions. Although Indonesia and Malaysia share historical and cultural links, their textbook narratives differ in their interpretations of colonial rule, its impacts, and its place in national history. This research addresses four main issues: the background of colonial arrival, the characteristics of colonial systems, the impacts of colonial rule, and similarities and differences in colonial state policies as presented in textbooks. Using a qualitative content analysis, this study examines selected secondary school history textbooks from Indonesia and Malaysia, published under different curricular frameworks. The analysis focuses on two main dimensions: how textbooks depict colonialism and how they construct particular perspectives on colonial experience. The findings show that Malaysian textbooks tend to present Western colonialism as a broader geopolitical process shaped by rivalry among imperial powers. British colonialism is described not only as exploitative but also as contributing to administrative modernization, territorial formation, and the development of a plural society. In contrast, Indonesian textbooks emphasize colonial exploitation, coercive policies, and popular resistance, especially under Dutch rule. Colonialism is largely portrayed as an oppressive force that generated suffering and stimulated nationalism. This study demonstrates that textbook narratives are closely related to national identity formation and educational ideology. It contributes to history education by showing that colonialism in textbooks is not merely presented as past events, but also as a value-laden narrative shaped by each nation’s political and historiographical priorities. Abstrak: Penelitian ini mengkaji bagaimana kolonialisme Barat dinarasikan dalam buku teks sejarah Indonesia dan Malaysia serta membandingkan perspektif yang dibangun dalam tradisi buku teks kedua negara. Meskipun Indonesia dan Malaysia memiliki keterkaitan historis dan kultural, narasi dalam buku teks keduanya menunjukkan penafsiran yang berbeda mengenai kolonialisme, dampaknya, dan posisinya dalam sejarah nasional. Penelitian ini berfokus pada empat aspek utama, yaitu latar belakang kedatangan kolonialisme, karakteristik sistem kolonial, dampak kekuasaan kolonial, serta persamaan dan perbedaan kebijakan kolonial yang disajikan dalam buku teks. Penelitian ini menggunakan pendekatan analisis isi kualitatif terhadap sejumlah buku teks sejarah tingkat sekolah menengah di Indonesia dan Malaysia yang diterbitkan dalam kerangka kurikulum yang berbeda. Analisis diarahkan pada dua dimensi utama, yaitu cara buku teks menggambarkan kolonialisme dan cara buku teks membangun perspektif tertentu terhadap pengalaman kolonial. Hasil penelitian menunjukkan bahwa buku teks Malaysia cenderung menampilkan kolonialisme Barat sebagai proses geopolitik yang lebih luas, dipengaruhi oleh persaingan antarkekuatan imperialis. Kolonialisme Inggris digambarkan tidak hanya eksploitatif, tetapi juga berkontribusi pada modernisasi administrasi, pembentukan wilayah, dan lahirnya masyarakat plural. Sebaliknya, buku teks Indonesia lebih menekankan eksploitasi